Automatic Chili Plant Watering Based On Internet Of Things (IoT) - Yuda Irawan; Eka Sabna; Ahmad Fauzan Azim; Refni Wahyuni; Naima Belarbi; Mbunwe Muncho Josephine (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Watering plants that are carried out by farmers on the land of thieves is still manual using human power, manual watering what is often used is to water with water through a water hose then the end of the hose is fitted with a water rotating device that is useful to rotate water so that it can reach many plants. To facilitate the watering of plants when farmers leave the city on agricultural land and know the level of soil moisture periodically, an automatic watering device based on IoT notification is made using the arduino Uno mikrocontroler. The whole tool is divided into several parts which consist of smartphone, esp, arduino uno revision three microcontroler, soil moisture,relay module, and pump. This tool works when the esp module connects to the internet, from esp then to siol moisture sensor if the level of moisture in the soil is detected below 70%, then provide information to the arduiono microcontroler to provide information on the humidity level to the LCD and the website www.pemuri.unaux.com as well as watering orders for plants. From the microcontroler then to the relay module to turn on the water pump. After the pump is running, the automation of the soil mositure sensor re-detects the soil moisture level, if it is above 70% then gives it again to the arduino microcontroler to give the command to turn off the pump. The results of the research show that esp can communicate well with arduino uno when it’s connected to the internet.